DIFERENTES BORDAS SOBRE A DINÂMICA DA CHUVA DE SEMENTES E SERAPILHEIRA EM FLORESTA OMBRÓFILA - Arpini, Juliana Kruger (2020)
The main impacts of fragmentation on forest diversity are related to border and barrier effects. Such effects cause changes, whether positive or negative, in the marginal composition of a fragment, which alters the successive secondary processes of regene